Influence of expiration date on the dimensional accuracy of elastomers (Research, Society and Development, 2020)
Impression materials are used to make models in different dentistry fields, with emphasis on oral rehabilitation with fixed and removable prostheses or dentures. The aim was to compare the dimensional accuracy of impressions based on polyvinylsiloxane (Express) and polyether (Impregum Soft) elastomers performed 2 years after their expiration date to impressions that did not exceed this period. Impressions were performed over matrix with metal tray; they were removed after polymerization and divided into 4 groups (n=5). Dimensional accuracy was evaluated through optical microscopy on the 20-µm line at 25-mm length (ISO 4823 standard). Dimensional accuracy values (%) were subjected to two-way ANOVA (material × expiration date) and Tukey's test (α=0.05). Based on the analysis of expiration date as independent factor (p=0.017), mean dimensional accuracy values recorded for elastomer impression 2 years after expiration date (99.89%) were statistically lower than values recorded for the non-expired one (99.92%). Changes resulting from the use of elastomers 2 years after their expiration date do not affect the dimensional accuracy of prostheses deriving from these impressions.